Zygote arrest 1 gene in pig, cattle and human: evidence of different transcript variants in male and female germ cells - Royere Dominique; Cadoret Veronique; Cognie Juliette; Pennetier Sophie; Mompart Florence; Thelie Aurore; Papillier Pascal; Perreau Christine; Dalbiès-Tran Rozenn; Roy-Sabau Monica; Uzbekova Svetlana; Monget Philippe; et al. (BMC, 2006)
Abstract Background Zygote arrest 1 (ZAR1) is one of the few known oocyte-specific maternal-effect genes essential for the beginning of embryo development discovered in mice. This gene is evolutionary conserved in vertebrates and ZAR1 protein is characterized by the presence of atypical plant homeobox zing finger domain, suggesting its role in transcription regulation. This work was aimed at the study of this gene, which could be one of the key regulators of successful preimplantation development of domestic animals, in pig and cattle, as compared with human. Methods Screenings of somatic cell hybrid panels and in silico research were performed to characterize ZAR1 chromosome localization and sequences. Rapid amplification of cDNA ends was used to obtain full-length cDNAs. Spatio-temporal mRNA expression patterns were studied using Northern blot, reverse transcription coupled to polymerase chain reaction and in situ hybridization. Results We demonstrated that ZAR1 is a single copy gene, positioned on chromosome 8 in pig and 6 in cattle, and several variants of correspondent cDNA were cloned from oocytes. Sequence analysis of ZAR1 cDNAs evidenced numerous short inverted repeats within the coding sequences and putative Pumilio-binding and embryo-deadenylation elements within the 3'-untranslated regions, indicating the potential regulation ways. We showed that ZAR1 expressed exclusively in oocytes in pig ovary, persisted during first cleavages in embryos developed in vivo and declined sharply in morulae and blastocysts. ZAR1 mRNA was also detected in testis, and, at lower level, in hypothalamus and pituitary in both species. For the first time, ZAR1 was localized in testicular germ cells, notably in round spermatids. In addition, in pig, cattle and human only shorter ZAR1 transcript variants resulting from alternative splicing were found in testis as compared to oocyte. Conclusion Our data suggest that in addition to its role in early embryo development highlighted by expression pattern of full-length transcript in oocytes and early embryos, ZAR1 could also be implicated in the regulation of meiosis and post meiotic differentiation of male and female germ cells through expression of shorter splicing variants. Species conservation of ZAR1 expression and regulation underlines the central role of this gene in early reproductive processes.